2012
DOI: 10.1016/j.str.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Integration of the PLCγ Interaction Domains Critical for Regulatory Mechanisms and Signaling Deregulation

Abstract: SummaryMultidomain proteins incorporating interaction domains are central to regulation of cellular processes. The elucidation of structural organization and mechanistic insights into many of these proteins, however, remain challenging due to their inherent flexibility. Here, we describe the organization and function of four interaction domains in PLCγ1 using a combination of structural biology and biochemical approaches. Intramolecular interactions within the regulatory region center on the cSH2 domain, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
119
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(135 citation statements)
references
References 27 publications
12
119
0
1
Order By: Relevance
“…ITC with mutated cSH2 and/or core polypeptides confirmed that the following residues are important at the cSH2/core interface: R748, R753, N728, S729 and D1019. Introducing substitutions in these residues into full length PLCγ and assaying for PLC activity in cells also showed that disrupting the cSH2/core interface imparted increased basal activity and increased EGF stimulated activity compared to wild type protein [29]. Therefore, a clearer picture of the molecular basis of auto-inhibition and activation emerges from these data ( Figure 1B).…”
Section: Structural Basis Of Auto-inhibition and Activation Of Plcγ Pmentioning
confidence: 92%
See 4 more Smart Citations
“…ITC with mutated cSH2 and/or core polypeptides confirmed that the following residues are important at the cSH2/core interface: R748, R753, N728, S729 and D1019. Introducing substitutions in these residues into full length PLCγ and assaying for PLC activity in cells also showed that disrupting the cSH2/core interface imparted increased basal activity and increased EGF stimulated activity compared to wild type protein [29]. Therefore, a clearer picture of the molecular basis of auto-inhibition and activation emerges from these data ( Figure 1B).…”
Section: Structural Basis Of Auto-inhibition and Activation Of Plcγ Pmentioning
confidence: 92%
“…Confirmation that the cSH2 is the domain in γSA directly involved in auto-inhibition came from NMR titration experiments [29]. The PLC-core from PLCγ was added independently into 15 N labelled domains of nSH2, cSH2 and spPH.…”
Section: Structural Basis Of Auto-inhibition and Activation Of Plcγ Pmentioning
confidence: 95%
See 3 more Smart Citations